2014
DOI: 10.20396/conex.v12i1.2184
|View full text |Cite
|
Sign up to set email alerts
|

Índices de crescimento estatural e estado nutricional de escolares de 6 a 14 anos escolares de 6 a 14 anos

Abstract: RESUMOO objetivo desse estudo foi investigar os índices de crescimento estatural e estado nutricional de escolares da rede municipal de ensino de Acopiara, no estado do Ceará. Participaram do estudo 622 escolares, dos quais 323 do sexo masculino e 299 do feminino com faixa etária entre 06 e 14 anos matriculados em duas escolas públicas do referido município. Para a avaliação do crescimento físico e estado nutricional este estudo adotou as variáveis massa corporal, estatura e os índices estatura para idade e IM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
(3 reference statements)
0
0
1
Order By: Relevance
“…Several other studies corroborate this finding 3,9,14,15 , also indicating, in particular, the larger number of school children with appropriate BMI. However, in a study by Nobre et al 16 , while the majority of their sample showed adequate nutritional status for age, their results diverge from the results of the present study in terms of reports that the condition of thinness or severe thinness was larger than the conditions of overweight and obesity.…”
Section: Discussioncontrasting
confidence: 99%
“…Several other studies corroborate this finding 3,9,14,15 , also indicating, in particular, the larger number of school children with appropriate BMI. However, in a study by Nobre et al 16 , while the majority of their sample showed adequate nutritional status for age, their results diverge from the results of the present study in terms of reports that the condition of thinness or severe thinness was larger than the conditions of overweight and obesity.…”
Section: Discussioncontrasting
confidence: 99%